Estrategias didácticas y motivación en la lectura en niños de sexto año de EGB de la escuela Zoila Ugarte de Landívar de la parroquia de Pózul en el Distrito 11D04 de Celica – Loja - Ecuador período 2023 – 2024. - Campoverde Becerra, Rosario Tomasa (2023)
The work called Didactic strategies and motivation in reading in children of the sixth year of Basic General Education (EGB) of the Zoila Ugarte de Landívar school of the Pózul parish in the District 11D04 of Celica - Loja - Ecuador allowed to know the didactic strategies in reading relationship used by teachers and motivation towards reading from the perspective of students and parents. It is important to use reading strategies that ensure that students are able to carry out a reading process where the analysis of the text allows a better understanding of what has been read. We conclude that it is important that teachers design activities that actively involve students during the reading process, intellectual curiosity must be awakened through new intellectual strategies that allow the student to investigate and therefore read. Children need stimulation towards reading, which will allow them to solve increasingly abstract and complex problems, since reading is a basic instrument for the construction of knowledge, at the same time the passion for reading is awakened in them, as well as Be more reflective from an early stage. It is necessary and essential to create strategies that manage to improve the teaching practice that encourages the reading process in children. Finally, we must take action through reading contagion to children and young people, at home and at school, but with enthusiasm, with delight, with fervor, so that they discover all the value richness that the text contains; and, above all, that they manage to experience the reading enjoyment that the teacher or parent feels when transmitting their reading to them, for which reason we propose a project called reading encouragement. Keywords: Reading strategies, Learning to read, Cognitive strategies